Аналіз екологічної безпеки відпрацьованих елементів живлення - Гринь, Григорій Іванович; Лавренко, Антоніна Олександрівна; Козуб, С. М.; Козуб, П. А.; Дейнека, Дмитро Миколайович; Бондаренко, Людмила Миколаївна (НТУ "ХПІ", 2009)
Analysis of information about toxicity of elements which constitute of nickel-metal-hydride battery and which used now as alternative for nickel-cadmium accumulator is done. The MPC of such substances for air and waters are presented, and comparative characteristics about toxicity of different groups of elements and their substances is done. Conclusion about necessity of complex approach to resolve ecological problem of utilization of all type of used source of power is done.
Keywords: екологія; навколишнє середовище; екологічна безпека; джерело живлення; елемент живлення; токсичність; нікель-метал-гідридні елементи; акумулятор